NARRATOR AND LANGUAGE IN THAI ONLINE LITERATURE - Piayura, Orathai; Sorthip, Marasri; Unthanon, Kanyarat; Tularak, Umarin (PEOPLE: International Journal of Social Sciences, 2018)
This article studies the narrators and the language used in Thai online Literature. The selected texts were randomly selected from short stories presented on the Gay Websites. The study focused on 6 short stories about male prostitutes. The result of the study revealed that the all of the stories were composed by using the narrators as the actors. The levels of language used in the narrative texts various from semi-informal to informal in order to form the identity of the narrators as male prostitutes. The adjectives to describe beauty and look were frequently used by the narrators.